2008
DOI: 10.1073/pnas.0805989105
|View full text |Cite
|
Sign up to set email alerts
|

Decyanation of vitamin B 12 by a trafficking chaperone

Abstract: The mystery of how the cyanide group in vitamin B12 or cyanocobalamin, discovered 60 years ago, is removed, has been solved by the demonstration that the trafficking chaperone, MMACHC, catalyzes a reductive decyanation reaction. Electrons transferred from NADPH via cytosolic flavoprotein oxidoreductases are used to cleave the cobalt-carbon bond with reductive elimination of the cyanide ligand. The product, cob(II)alamin, is a known substrate for assimilation into the active cofactor forms, methylcobalamin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
176
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(190 citation statements)
references
References 29 publications
10
176
1
3
Order By: Relevance
“…Hence, it is possible that M. barkeri strain Fusaro and the Sporomusa isolates provided the D. mccartyi strains with not yet identified compounds that enhance growth yields. Another possible explanation for the lower growth yields observed with CN-Cbl is the cell's energetic burden associated with the replacement of the upper cyanide ligand [33].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is possible that M. barkeri strain Fusaro and the Sporomusa isolates provided the D. mccartyi strains with not yet identified compounds that enhance growth yields. Another possible explanation for the lower growth yields observed with CN-Cbl is the cell's energetic burden associated with the replacement of the upper cyanide ligand [33].…”
Section: Discussionmentioning
confidence: 99%
“…The reductive decyanation of CNCbl is catalyzed by the MMACHC protein in the presence of a flavoprotein reductase and NADPH [ 36 ]. The authors reported that cblC bound both MeCbl and AdoCbl inducing their base-off conformation [ 36 ]; however, it did not catalyze the dealkylation of MeCbl and AdoCbl, the two major dietary forms of Cbl. This intriguing finding was re-examined via ex vivo studies [ 37 ], and a new function was uncovered for the cblC protein: MMACHC is also a Cbl dealkylase [ 37 ].…”
Section: Biophysical and Structural Characterization Of The B 12 -Promentioning
confidence: 99%
“…The mystery of how decyanation of cyanocobalamin (CNCbl) occurs was recently solved by the in vitro studies of Kim et al [ 36 ]. The reductive decyanation of CNCbl is catalyzed by the MMACHC protein in the presence of a flavoprotein reductase and NADPH [ 36 ].…”
Section: Biophysical and Structural Characterization Of The B 12 -Promentioning
confidence: 99%
“…Similarly, in the CblC-catalyzed dealkylation reaction, the glutathione thioether forms upon transfer of the alkyl group in addition to cob(I)alamin. When CNCbl is in the active site, electrons provided by free or protein-bound reduced flavin promote reductive homolytic cleavage, leading to cyanide elimination (13,35). Based on UV-visible and EPR spectroscopy, baseoff cob(II)alamin has been identified as the other product of the reductive elimination, consistent with a homolytic cleavage reaction mechanism.…”
Section: Early Steps In the Cytosolic Processing Of Cobalaminmentioning
confidence: 73%
“…The identity of the upper or ␤-axial ligand varies and includes cyano, aquo, methyl, and 5Ј-deoxyadenosyl groups. Ironically, 6 decades after its discovery, the origin and biological relevance of the cyano group remain unknown, although we have recently described a decyanase activity in the processing pathway (13), which allows utilization of CNCbl used in vitamin supplements. As the cobalt oxidation state decreases from 3 ϩ 3 2 ϩ 3 1 ϩ , the coordination number typically decreases from 6 3 5 3 4.…”
Section: B 12 Chemistry and Catalysismentioning
confidence: 99%